Facing challenges and complexities in retention of novice teachers - McDonald, Denise Tutka (Research in curriculum and instruction., 2019)
"The chapters in the book present in-depth examination of novice teachers' experiences in Houston area schools during their first-through-third year of teaching. Their professional challenges and the unique conditions in which they must navigate their developing and sometimes fragile teacher identity are comprehensively explored"--